PERANCANGAN IKLAN KAMPANYE PENGHARGAAN ADIWIYATA KABUPATEN GRESIK MELALUI ANIMATION EXPLAINER SEBAGAI UPAYA MENINGKATKAN KESADARAN LINGKUNGAN HIDUP - Ali, M Fauzil; Bahruddin, Muh; Dewanto, Thomas Hanandry (Jurnal Art Nouveau, 2015)
Abstract: The goal of the design campaign advertising Adiwiyata Gresik is to raise awareness of the environment in the school district. Further research was conducted using qualitative research methods that do interviews, observation, documentation, and literature to obtain the data used to support the manufacture of the design concept of the ad campaign. Data were analyzed using several stages, namely data reduction, data presentation, and conclusion. After analyzing the data, found a design concept or keyword advertising campaign is